Probabilistic Analysis of the 6061 Aluminium Alloy Tensile Test with Random Initial Microdefects - Strąkowski, M.; Kamiński, M. (Wydawnictwo Politechniki Łódzkiej, 2021)
The main aim of this paper was to investigate an application of the generalized higher order iterative generalized stochastic perturbation technique in numerical simulation of 6061 aluminum alloy plastic behavior with structural initial microdefects. Gurson-Tvergaard-Needleman constitutive porous material model implemented in ABAQUS system has been employed for this purpose with its 2D triangular and quadrilateral elements. A volume fraction f0 of the initial microdefects naturally appearing in the material has been adopted as the input random variable having symmetric but not necessary Gaussian distribution. A verification of its uncertainty influence on statistical scattering of material specimen deformations, stresses and void volume fractions has been carried out thanks to the common usage of the FEM system ABAQUS and computer algebra system MAPLE 2019. The 10th order Iterative Stochastic Perturbation Technique has been compared with Monte Carlo Simulations and Semi-Analytical Method to analyze uncertainty in extreme stresses and deformations within the tensioned material coupon.
Keywords: porosity; GTN-material model; stochastic finite element method; aluminium alloy; porowatość; model materiału GTN; stochastyczna metoda elementów skończonych; stop aluminium